The Content of Heavy Metals, Arsenic, and Aluminum in Mint Leaves and Products - V. M. Shchukin; E. A. Blinkova; N. E. Kuz’mina; A. I. Luttseva (Регуляторные исследования и экспертиза лекарственных средств, 2022)
Mint is a medicinal herbal drug; and its leaves are also widely used in the food and cosmetic industries. Medical literature states that mint is naturally resistant to toxic elements and capable of accumulating them in significant amounts. The aim of the study was to compare heavy metals, arsenic, and aluminum contents in mint leaves and products. Materials and methods: the study covered peppermint leaves, tinctures, and oils, as well as teas and dietary supplements made of different varieties of mint. Elemental analysis was performed according to the procedure of inductively coupled plasma mass spectrometry (ICP-MS) developed by the authors. Results: the authors studied the compliance of the experimentally established contents of heavy metals, arsenic, and aluminum in peppermint leaves and products to the requirements of Russian and foreign regulatory documentation. Nonparametric Spearman correlation coefficients were calculated to characterise the interaction between chemical elements. Conclusions: arsenic contents in mint leaves may exceed the limit given in the State Pharmacopoeia of the Russian Federation, 14th ed. It is supposed that the increased contents are not a result of the anthropogenic factor, but a specific characteristic of this plant. The study demonstrated synergistic absorption of aluminum, iron, and vanadium, as well as copper and zinc by mint. It was established that manganese had an antagonistic effect on the absorption of nickel, lead, and cobalt by mint.